English 'iron rod' welfare versus Italian 'colander' welfare: understanding the intra-European mobility strategies of unaccompanied young migrants and refugees. (October 2022) - Allsopp, Jennifer
The experiences of unaccompanied young migrants and refugees challenge the idea of a common European asylum policy but also show that traditional welfare typologies used to account for differences in welfare across states fail to account for the lived experiences of this group. They do not consider the shifting categorizations of young migrants in institutional terms, nor how the stratification of their social rights plays out over place and time. Moreover, current welfare typologies give inadequate attention to the increasing intersection of the labour market and opportunities for regularization, the relative importance and role of the state in the welfare mix, and the nexus of access to welfare and immigration enforcement. This article draws on qualitative longitudinal research in England and Italy to argue that rather than experiencing welfare through the lens of Liberal (England) versus Conservative or Mediterranean (Italy) regimes, unaccompanied young migrants and refugees in these countries are better understood as navigating different systems of 'iron rod welfare' and 'colander welfare'. In England, the nexus between welfare and legal status is policed by an iron rod on one side of which exists a plethora of social rights, but on the other the risk of a proactive detention and deportation regime. In Italy, meanwhile, the holes of the colander denote gaps in protection but also possibilities to navigate alternative welfare strategies independently of the state. The ability to act independently of the state is an important but under-theorized capability for this population, for whom the state is a more ambiguous actor than is traditionally considered in European social policy.